2023
DOI: 10.1186/s12903-023-02870-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of unilateral removable partial dentures versus removable partial dentures with major connector on oral health-related quality of life of elder patients: a clinical study

Abstract: Objective This study aimed to establish the survival rate of unilateral removable partial dentures (u-RPD) comparative with bilateral RPD (bi-RPD) with major connector in elder patients, as well as to determine both their treatment satisfaction and oral health. Methods The study sample included 17 patients treated with u-RPD and 17 patients treated with bi-RPD with a major connector. The patients were followed over five years with recalls every 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…It was reported that periodontal parameters including gingival index, tooth mobility, and clinical attachment loss were significantly affected at day-60 compared with baseline. 19,20…”
Section: Page-120mentioning
confidence: 99%
“…It was reported that periodontal parameters including gingival index, tooth mobility, and clinical attachment loss were significantly affected at day-60 compared with baseline. 19,20…”
Section: Page-120mentioning
confidence: 99%
“…Change in the biofilm, alter quantitative and qualitative changes in plaque cause harm to the abutments thus the reason for failure of RPDs is the loss of abutments. In contrast some researchers reported that no pathologies could result only by removable dentures alone as long as good hygiene protocols are being followed 10 . These adverse effects of removable partial denture can be prevented by careful instructions to the patients regarding importance of oral hygiene, periodic recalls, professional scaling and polishing procedures and optimum fabrication of removable partial denture design with less complicated design 11 .…”
Section: Introductionmentioning
confidence: 95%